Nanoscale Structure and Dynamics of Model Membrane Lipid Raft Systems, Studied by Neutron Scattering Methods - Ahmadi, Delaram; Thompson, Katherine C.; García Sakai, Victoria; Schweins, Ralf; Moulin, Martine; Haertlein, Michael; Strohmeier, Gernot A.; Pichler, Harald; Forsyth, V. Trevor; Barlow, David J.; Lawrence, M. Jayne; Foglia, Fabrizia (Frontiers in Physics, 2022)
QENS and SANS, in combination with isotopic contrast variation, have been used to determine the structure and dynamics of three-component, lipid membranes in the form of vesicles comprising an unsaturated (palmitoyl-oleoyl-phosphatidylcholine (POPC) or dioleoyl-phosphatidylcholine (DOPC)), a saturated phospholipid (dipalmitoyl-phosphatidylcholine (DPPC)), and cholesterol, as a function temperature and composition. SANS studies showed vesicle membranes composed of a 1:1:1 molar ratio of DPPC:DOPC:cholesterol and a 2:2:1 molar ratio of DPPC:POPC:cholesterol phase separated, forming lipid rafts of ~18 and ~7nm diameter, respectively, when decreasing temperature from 308 to 297K. Phase separation was reversible upon increasing temperature. The larger rafts observed in systems containing DOPC are attributed to the greater mis-match in lipid alkyl chains between DOPC and DPPC, than POPC and DPPC. QENS studies, over the temperature range 283-323K, showed the resulting data was best modelled by two Lorentzian functions: a narrow component, describing the ‘in-plane’ lipid diffusion, and a broader component, describing the lipid alkyl chain segmental relaxation. The overall ‘in-plane’ diffusion, was found to show a significant reduction upon increasing temperature due to the vesicle membranes transitioning from containing rafts to one where the component lipids are homogeneously mixed. Using different isotopic combinations allowed the measured overall reduction of in-plane diffusion to be resolved as being the result of an increase in diffusion of the saturated DPPC lipid and a corresponding decrease in diffusion of the unsaturated DOPC/POPC lipid. As the rafts are considered to be composed principally of saturated lipid and cholesterol, the breakdown of rafts decreases the exposure of the DPPC to cholesterol whilst increasing the exposure of cholesterol to unsaturated lipid. These results show the sensitivity of lipid diffusion to local cholesterol concentration and the importance of considering the local, rather than global, composition of a membrane on the diffusion of lipids contained within. The novel combination of SANS and QENS used here is an informative and non-intrusive means to characterize the structure of and dynamics occurring in phase separated model membranes designed to mimic the lateral heterogeneity of lipids seen in cellular membranes – a heterogeneity that can carry pathological consequences.